Health related quality of life of women in TEACH, a randomised placebo controlled adjuvant trial of lapatinib in early stage Human Epidermal Growth Factor Receptor (HER2) overexpressing breast cancer. Issue 6 (April 2015) - Boyle, Frances M.; Smith, Ian E.; O'Shaughnessy, Joyce; Ejlertsen, Bent; Buzdar, Aman U.; Fumoleau, Pierre; Gradishar, William; Martin, Miguel; Moy, Beverly; Piccart-Gebhart, Martine; Pritchard, Kathleen I.; Lindquist, Deborah; et al.
Summary Background To evaluate health related quality of life (HRQOL) in TEACH, a phase III randomized placebo controlled trial of 12 months of adjuvant lapatinib in HER2 positive (HER2+) early breast cancer which demonstrated marginal benefit in disease-free survival. Methods Women on TEACH completed the Short Form 36-item health survey (version2; SF-36v2) at the baseline, six and 12 months after therapy initiation and six monthly thereafter. Mean changes were compared between treatment groups for two summary measures (Physical and Mental Component Summary scores; PCS and MCS) and eight domain measures (physical functioning, role physical, bodily pain, general health, vitality, social functioning, role emotional and mental health), and in patients discontinuing therapy. A five-point change was deemed a Minimally Clinically Important Difference (MCID). Response analysis compared the proportion of patients demonstrating a MCID in HRQOL, and a regression analysis identified predictors of worsening HRQOL. Findings 3074 (97%) subjects completed baseline SF-36v2. During the initial 12 months, summary SF-36v2 scores decreased in both arms but did not reach Minimally Clinically Important Difference (MCID) despite significant incidences of diarrhoea and rash in lapatinib treated patients. At six months, women receiving lapatinib had more significant reductions (p < 0.01 versus placebo) in social functioning. Early treatment discontinuations were more frequent on lapatinib (32% versus 18%), and were associated with more substantial decrements of HRQOL in both arms. For those discontinuing primarily due to adverse events, decrements in HRQOL reached MCID in Mental Summary scores (MCS) only. Lower baseline HRQOL was a significant predictor of worsening HRQOL (p < 0.05). Interpretation Despite frequent but usually mild toxicities, adjuvant lapatinib is not associated with clinically significant decreases in overall HRQOL. These placebo-controlled results may also help to inform physicians and patients using lapatinib in metastatic HER2 positive breast cancer. Funding GlaxoSmithKline. The AVON Foundation NY supported PEG, DF and BM and The Friends of the Mater Foundation supported FB.